Observation of negative capacitance in antiferroelectric PbZrO3 Films - Leilei Qiao (Nature Portfolio, 2021)
The observation of negative capacitance effect is focused on the ferroelectrics, while the antiferroelectrics based on Landau switches may have negative capacitance effect. Here, the authors report the static and transient negative capacitance effect in antiferroelectric PbZrO3 and reveal its origin.